Clinical research progress on acute exudative polymorphous vitelliform maculopathy - JIANG Li; YANG Mingming (Yanke Xuebao)
Acute Exudative Polymorphous Vitelliform Maculopathy (AEPVM) is a clinically rare fundus disease characterized primarily by neurosensory detachment in the macular area and accumulation of vitelliform material in the posterior pole. The exact cause is unclear and may be related to systemic infections, autoimmune responses, or paraneoplastic syndromes. Clinical manifestations usually include mild vision loss or photophobia, and yellow-white deposits can be seen in the posterior pole of the fundus, exhibiting relatively higher autofluorescence in spontaneous fluorescence. Fundus fluorescein angiography typically does not show leakage of fluorescein in the lesion area. Optical coherence tomography (OCT)examination can reveal thickening of the ellipsoid zone and cystic changes within the neurosensory layer. Currently, there is no explicit treatment plan. This article reviews the clinical presentation, imaging characteristics, diagnosis and differential diagnosis, pathogenesis, and treatment-related research progress of acute exudative polymorphous vitelliform maculopathy. In summary, the natural course of acute exudative polymorphous vitelliform maculopathy is complex and diverse, and its diagnosis and differential diagnosis remain challenging. A deeper understanding of the clinical presentations and imaging characteristics of acute exudative polymorphous vitelliform maculopathy will facilitate further research and exploration to clarify its pathological mechanisms and identify effective treatment methods in the future.